2000
DOI: 10.2307/3871141
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydomonas reinhardtii Nar1 Gene Encodes a Chloroplast Membrane Protein Involved in Nitrite Transport

Abstract: A key step for nitrate assimilation in photosynthetic eukaryotes occurs within chloroplasts, where nitrite is reduced to ammonium, which is incorporated into carbon skeletons. The Nar1 gene from Chlamydomonas reinhardtii is clustered with five other genes for nitrate assimilation, all of them regulated by nitrate. Sequence analysis of genomic DNA and cDNA of Nar1 and comparative studies of strains having or lacking Nar1 have been performed. The deduced amino acid sequence indicates that Nar1 encodes a chloropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Lamattina et al (2003) suggested that changes in NR activity could be modulated by nitrite availability. When the plant is photosynthetically active, nitrite produced by NR is immediately taken up by the chloroplast and reduced to ammonium (Rexach et al, 2000). However, nitrite accumulation can be expected when photosynthetic activity is low, so that NR-mediated conversion of nitrite to NO could take place in these conditions (Lillo et al, 2003;Lea et al, 2004) and NO could then repress NIA1 transcription, the whole process forming a feedback loop.…”
Section: A Regulation Model For Nia1 Transcription Involves Ammoniummentioning
confidence: 99%
“…Lamattina et al (2003) suggested that changes in NR activity could be modulated by nitrite availability. When the plant is photosynthetically active, nitrite produced by NR is immediately taken up by the chloroplast and reduced to ammonium (Rexach et al, 2000). However, nitrite accumulation can be expected when photosynthetic activity is low, so that NR-mediated conversion of nitrite to NO could take place in these conditions (Lillo et al, 2003;Lea et al, 2004) and NO could then repress NIA1 transcription, the whole process forming a feedback loop.…”
Section: A Regulation Model For Nia1 Transcription Involves Ammoniummentioning
confidence: 99%
“…take into Chlamydomas chloroplasts appears to be regulated only under certain conditions, i.e. limiting nitrogen and carbon supply [32].…”
Section: Discussionmentioning
confidence: 99%
“…LCIA, or NAR1.2, is involved in the bicarbonate transport system in chloroplasts (Duanmu et al, 2009) but is not regulated by nitrogen availability, and has been identified as a low-CO 2 -inducible gene by expressed sequence tag (EST) analysis . However, NAR1 genes generally involve members of the formate/nitrite transporter family (Rexach et al, 2000). In fact, LCIA-expressing Xenopus oocytes display both low-affinity bicarbonate transport and high-affinity nitrite transport activities (Mariscal et al, 2006), suggesting that LCIA is involved in both bicarbonate uptake and nitrite uptake induced under low-CO 2 conditions.…”
Section: Molecular Mechanisms For High-co 2 Responsesmentioning
confidence: 99%